Physiological and health‐related response of broiler chickens fed diets containing raw, full‐fat soya bean meal supplemented with microbial protease. Issue 2 (10th October 2017) - Erdaw, M. M.; Perez‐Maldonado, R. A.; Iji, P. A.
Summary: A 2 × 3 factorial study (protease: 0 or 1, 5000 PROT/kg and raw full‐fat soya bean meal [RSBM] replacing the commercial SBM at 0, 45 and 75 g/kg of diet) was conducted to examine the performance of broilers. Phytase (2000 FYT/kg) was uniformly added to each diet, each also replicated six times, with eight birds per replicate. Birds were raised in climate‐controlled rooms using sawdust as the bedding material and offered starter, grower and finisher diets. Feed intake (FI) and body weight gain (BWG) were reduced ( p  < .05) due to increasing levels of RSBM, but feed conversion ratio (FCR; 0–35 days) was unaffected. Over the first 24 days, neither RSBM nor protease supplementation affected ( p  > .05) mortality, footpad dermatitis or intestinal lesions in birds. At day 24, the weight, length, width and strength of tibia bone were reduced in chickens that received an elevated level of RSBM (75 g/kg of diet), but this was not significant at day 35. At day 24 ( p  < .05) and 35 ( p  < .01), Ca concentration in the litter was reduced when the RSBM level was increased in the diet, but P content was not affected. On days 24 ( p  < .05) and 35 ( p  < .01), the N content in litter was also increased with increase in dietary RSBM. Protease supplementation increased ( p  < .05) the uric acid concentration in the litter (at day 35), but the reverse was the case for ammonia concentration. Overall, the results of this study indicate that there are no major health‐related risks, associated with the replacement of commercial SBM with RSBM (≤25%) in broiler diets.